2022
DOI: 10.3389/fimmu.2022.985226
|View full text |Cite
|
Sign up to set email alerts
|

Durable antibody and effector memory T cell responses in breastmilk from women with SARS-CoV-2

Abstract: BackgroundGiven that only 25% of pregnant women elect to receive a COVID-19 vaccine, maternal SARS-CoV-2 infection remains an important route of conferring protective passive immunity to breastfed infants of mothers who are not vaccinated.MethodsWe enrolled 30 lactating participants between December 2020 and March 2021 who had a positive PCR-test and their first COVID-19 symptoms within the previous 21 days. Participants were asked to provide serial bilateral milk samples at 12 timepoints (~ every 3 days) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In a recently published paper, it was observed that T cells play a more significant role in controlling COVID-19 than other immune cells, and therefore along with measurement of neutralizing antibodies that are known to offer protection, it is important to know the T cell count. In a recent study, the breastmilk before and after COVID-19 infection found that there was an increase in the percentage of macrophages expressing INF-alpha and this signifies the role of macrophages as the main component in the innate immunity of the milk [ 15 ].…”
Section: Discussion (Table 1 )mentioning
confidence: 99%
“…In a recently published paper, it was observed that T cells play a more significant role in controlling COVID-19 than other immune cells, and therefore along with measurement of neutralizing antibodies that are known to offer protection, it is important to know the T cell count. In a recent study, the breastmilk before and after COVID-19 infection found that there was an increase in the percentage of macrophages expressing INF-alpha and this signifies the role of macrophages as the main component in the innate immunity of the milk [ 15 ].…”
Section: Discussion (Table 1 )mentioning
confidence: 99%
“…All mothers who had recovered from COVID-19 had antibodies in their breast milk, providing opportunities to use this as a treatment for critically ill infants or to prevent severe illness in susceptible infants. Breast milk also contained high levels of IgA antibodies, which were particularly effective against diseases attacking the respiratory tract, such as COVID-19 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies must compare the potency of the antibodies present in breast milk to those present in the blood. The levels of sIgA in breast milk surpassed those found in plasma, and sIgA provided substantial protection for the respiratory tract [7,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations